Reviewing the research in children's spirituality (2005-2015): proposing a pluricultural approach - Mata-McMahon, Jennifer (International journal of children's spirituality, 2016)
Research on children's spirituality seems to continue to be scarcely represented in the field of early childhood. In reviewing the literature, looking at empirical data-driven studies, this paper compiles an international review of the work completed in the last 10 years (2005-2015) on the topic of children's spirituality. The research-based works reviewed are analysed and sorted taking into account: research methods, participant demographics (age, gender, ethnicity) and location (urban vs. suburban/rural, school vs. home), yet are presented in categories found related to their topic of study: (1) spiritual meaning-making and relationships to/with God, (2) children's spirituality in education and (3) identity formation and sense of self. Finally, identification of gaps in the research literature regarding the study of children's spirituality is presented. As well, avenues for future research are proposed, identifying methods and approaches. Also, the term pluricultural as a means to guide researchers in making sense of the complex phenomenon that is children's spirituality is introduced.